Development of Canva-Based E-Module to Improve PAI Learning Outcomes for Class XI at SMK Patria Gadingrejo - Vivi Wulandari; Imam Syafe'i; Siti Roudhotul Jannah (Assyfa Journal of Islamic Studies, 2026)
This study aims to develop a Canva-based e-module for Islamic Religious Education (PAI) subjects to improve learning outcomes for class XI students at SMK Patria Gadingrejo. The background of this research is the low student learning outcomes in PAI subjects caused by the use of conventional modules that are less attractive and the low reading interest among students in the digital era. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques include observation, interviews, questionnaires, and documentation. The research subjects were 30 class XI students at SMK Patria Gadingrejo. The results showed that the Canva-based e-module was declared very feasible by material experts with an average percentage of 100% in the "Very Feasible" category and by media experts with an average score of 99% in the "Very Feasible" category. The results of small group trials showed positive responses from teachers with a percentage of 99% and from students with a percentage of 99%. The results of large group trials showed that all 30 students (100%) achieved scores above the Minimum Completeness Criteria (KKM) with an average score of 87.5. This study concludes that the Canva-based e-module on the theme "Marriage Provisions in Islam" is effective in improving the learning outcomes of class XI PAI students at SMK Patria Gadingrejo and is feasible to use as an innovative learning medium in the digital era.